2020
DOI: 10.1093/cdn/nzaa053_090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eggs on Growth Among Infants 6–12 months of Age in Rural Bangladesh: A Cluster Randomized Controlled Trial

Abstract: Objectives To assess the impact of daily egg supplementation on infant growth from 6–12 months of age in Bangladesh. Methods A cluster randomized controlled trial was conducted in rural Bangladesh to test the effect of daily egg supplementation and nutrition education versus nutrition education alone on linear growth and stunting prevalence among infants. Infants were enrolled at 3 months of age and assigned to a trial arm ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The increase in WAZ and WHZ recorded in this trial was four and five times, respectively bigger than what was found through supplementation of eggs to 6–12 months old children in rural Bangladesh [ 35 ]. One-egg-a-day supplementation in Ecuador increased WAZ, WHZ, and LAZ by 0.61, 0.33 and 0.63, respectively and reduced stunting and underweight by 47% and 74%, respectively; the biggest effect sizes reported so far from egg interventions [ 14 ].…”
Section: Discussionmentioning
confidence: 62%
“…The increase in WAZ and WHZ recorded in this trial was four and five times, respectively bigger than what was found through supplementation of eggs to 6–12 months old children in rural Bangladesh [ 35 ]. One-egg-a-day supplementation in Ecuador increased WAZ, WHZ, and LAZ by 0.61, 0.33 and 0.63, respectively and reduced stunting and underweight by 47% and 74%, respectively; the biggest effect sizes reported so far from egg interventions [ 14 ].…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, a recent review concludes that egg consumption affects not only the child's linear growth but also has a significant impact on brain development 43 . However, an experimental study in Bangladesh found that providing a daily egg to infants for 6 months had an effect on ponderal but not linear growth 44 and trials in Malawi and Zambia found that providing 1 egg per day to children had no overall effect on linear growth 45 . This finding was also congruent with the evidence that consumption of generic animal source foods (ASF) (dairy, meat/fish, and egg) has a strong statistical association with stunting and such that consuming multiple ASFs is more advantageous than any single ASF 46 .…”
Section: Discussionmentioning
confidence: 99%